Effect of resistance load on biomechanical characteristics of racing wheelchair propulsion over a roller system - Chow, J. W.; Millikan, T. A.; Carlton, L. G.; Chae, W. S.; Morse, M. I. (Journal of Biomechanics, 2000)
The purpose of this study was to examine how resistance load influenced the kinematic characteristics and the activity of selected muscles (flexor and extensor carpi radialis, biceps brachii, triceps brachii, antero-middle and postero-middle deltoids, pectoralis major, and upper trapezius) during maximum effort racing wheelchair stroking using 3D videographic and surface EMG techniques. Fifteen male experienced wheelchair racers served as subjects and three consecutive stroke cycles were analyzed for two load conditions. In contrast to previous studies where variations in speed were a result of variations in pushing effort or disability classification, a reduction in stroking speed caused by increasing load did not result in a decrease in stroking frequency. Increases in load significantly influenced the push and recovery times but not the stroke time or frequency. The vertical ranges of motion and vertical velocities at initial hand contact of the upper extremity joints decreased significantly from light to heavy resistance conditions. These results suggest that the vertical motion is influenced greatly by the load. Various degrees of muscle co-contractions were observed in most phases of the stroke cycle. The activation pattern of the deltoid muscle was different from what has been previously reported, probably because of the exaggerated forward lean trunk position adopted by our subjects. Although the overall EMG activity remained the same or decreased when the resistance was increased, stroking under a heavy resistance load is likely to be more demanding physiologically because of the greater push time-recovery time (work-rest) ratio with increasing resistance.